Palaeoenvironmental evolution and stage-dependent organic matter enrichment in the Late Permian Longtan Formation, Upper Yangtze Block, South China - Hai-Feng Chen; Xin Jin; Marcello Caggiati; Ting-Cong Ren; Bo Luo; Lin-Hao Fang; Hua-Wen Cao; Yang Liu; Chang-Cheng Huang; Bin Xiao; Zi-Han Ma; Hui-Dong Yu; et al. (Sedimentary Geology, 2026)

Seismic rehabilitation of severely earthquake-damaged ductile RC T-shaped beams using mechanically anchored CFRP strips: Anchorage requirements and experimental validation - Chien-Kuo Chiu; Yi-Feng Lin; Hsin-Fang Sung; Lung-Cheng Hsieh (Engineering Structures, 2026)

VMMFNet: a lightweight dual-branch multispectral fusion network for multi-stage detection of pine wilt disease - Jiajun Wang; Guanyi Cheng; Fang Wang; HongPing Zhou; Haifeng Lin (Computers and Electronics in Agriculture, 2026)

Unlocking the potential in municipal reclaimed water electrolysis for hydrogen production: Identification of the primary water matrix - Zongping Wang; Haoran Chen; Zhenbin Chen; Yunfei Li; Ang Lu; Yujie Cheng; Guosen Zhang; Ge Li; Shunjie Zhu; Lin Li; Lizhi Huang; Jiakun Fang; et al. (Water Research, 2026)

Rhizophagus intraradices differentially promotes growth and phosphorus uptake in Camellia oleifera under low versus adequate phosphorus supply - Wan-Lin Fu; Ying-Ning Zou; Shi-Qi Pu; Fang-Ling Wang; Zhi-Yan Xiao; Jun-Yong Cheng; Mei-Hua Yang; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Rhizosphere, 2026)

First visualization of intact sperm storage tubules in the duck oviduct: A fluorescent labeling approach for targeted SST sampling - Hsiu-Lien Herbie Lin; Chin-Hui Su; Shih-Yi Huang; Ya-Hsin Kuo; Liang-Yuan Wei; Yi-Ying Chang; Ching-Wei Chang; Jeng-Fang Huang; Pascal Mermillod; Chih-Hsiang Cheng (Animal Reproduction Science, 2026)

Reclamation to aquaculture ponds accelerates losses of Fe-bound organic carbon in estuarine wetlands - Junma Chen; Liwen Cheng; Yunying Fang; Ji Chen; Weiqi Wang; Yi Zheng; Shiyu Chen; Lin Wang; Jordi Sardans (Water Research, 2026)

Unveiling precursor-derived PFAS burdens in landfill leachate: TOP assay reveals ultrashort-chain PFAS and DTRO removal limitations across 11 Chinese cities - Ying Zhang; Nemin Luo; Bin Yan; Lei Wang; Haolong Zhang; Mingyuan Lin; Ting Fang; Zhenchang Zhong; Huiyan Cheng; Yan Lin (Journal of Environmental Sciences, 2026)

Comprehensive analysis of microbial community assembly and metabolic dynamics reveals the effects of environmental acidity on flavor formation pathways during the Zhejiang rosy vinegar fermentation process - Cheng-Hao Jin; Yong-Zhu Zhang; Wen-Tian Song; Peng Wang; Chang-Ling Wu; Lin-Mei Liang; Wei Feng; Xiao-Tao Sun; Xing-Quan Liu; Guan-Yu Fang (Food Research International, 2026)

Associations of prenatal individual and mixture per- and polyfluoroalkyl substances (PFAS) exposures with fetal growth trajectories: Modifying effects of maternal micronutrient status - Zhen-Hua Li; Hai-Yang Weng; Chun-Yong Wang; Xiao-Yu Zhao; Guo-Peng Gao; Kai Huang; Mao-Lin Chen; Fang-Biao Tao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Research, 2026)

Multifunctional BQD interlayer enables high-resolution high-efficiency QLEDs:Eliminating EML void defects and optimizing interfacial carrier transport - Yue Chen; Yuting Bai; Zunxian Yang; Luxi Yuan; Ye Chen; Xudong Jiang; Jiajie Hong; Benfang Liu; Zhiyu Yuan; Jinzhu Gao; Zhezhou Fang; Runsen Yu; et al. (Chemical Engineering Journal, 2026)

Interdecadal winter temperature variability driven by the East China Sea Mode: A global perspective - Keyan Fang; Hao Wu; Shuheng Lin; Jun Cheng; Jane Liu; Deliang Chen; Jinbao Li; Cesar Azorin-Molina; Zheng Zhao; Frode Stordal; Shuo Hao; Nicole Davi; et al. (Science China Earth Sciences, 2026)

The Hippo–Yki pathway governs growth and cell fate in the posterior silk gland of the silkworm - Yan Ma; Zhiyong Zhang; Wenhui Zeng; Zhou Fang; Xin Yu; Lin Cheng; Zehui Ma; Qipeng Zeng; Dena Jiang; Yiyun Tang; Jie Hu; Chen Zhao; et al. (Insect Biochemistry and Molecular Biology, 2026)

Effect of Excavation Sequence and Bolt Support on Surrounding-Rock Stability of a Double-Tunnel System in Jointed Rock Mass - Feng Jiang; Tian-lin Huang; Hai-zhen Huang; Ji-song Wang; Peng He; Gang Wang; Chun-gui Li; Ting-fang Liu; Cheng-cheng Zheng; Zhi-yong Xiao (Applied Geophysics, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Atmospheric Boundary Layer Eco-Environment Shanghuang Observatory: An Integrated Multiscale Research Platform in Southeastern China for Understanding Boundary Layer Processes, Atmospheric Chemistry Feedback, and Extreme Weather–Climate Linkages - Zifa Wang; Xiaole Pan; Yele Sun; Jinyuan Xin; Hang Su; Junji Cao; Jie Li; Ting Yang; Hang Liu; Weijie Yao; Weiqi Xu; Xueshun Chen; et al. (Advances in Atmospheric Sciences, 2026)

A new Rhizomucor miehei lipase immobilized on anhydride-hydrophobized amino supports: Optimization, characterization and application in preparing medium- and long-chain structured lipids - Yiyi Lin; Xiansi Gao; Zheling Zeng; Di Kuang; Kai Fang; Tianyi Song; Ping Yu; Deming Gong; Cheng Zeng; Xianghui Yan (Food Bioscience, 2026)

Urban-suburban-rural gradient variations in mortality associated with compound exposure to heat wave and ozone pollution: A case-crossover study using small-area assessment - Kang Ma; Fengman Fang; Xiuya Xing; Yuesheng Lin; Cheng He; Youru Yao; Fei Tong; Jingli Zhu; Huadong Wang; Feiyan Zhang; Ruoxi Li (Journal of Environmental Management, 2026)

Al-doped α-MnO2 for low-temperature catalytic oxidation of formaldehyde - Zhengnan Lin; Zhao Zheng; Junchen Li; Cheng Zhang; Qingyan Fang; Peng Tan; Gang Chen (Journal of Environmental Chemical Engineering, 2026)

Effects of baking degree of Longjing green tea on flavor attributes, antioxidant activity and advanced glycation end products - Ran Wei; Xiao-Yu Zhong; Kayama Kayama; Yu-Hong Lin; Fang-Ting Qin; Zhu-Cheng Su; Yong-Quan Xu (Food Research International, 2026)

Targeting PTGS2/NF-κB Pathway: MG-132’s Role in Reducing Ischemic Stroke Injury - Yong-Sheng Wang; Yuan-Cheng Huang; Yong-Qi Wang; Yi-Xuan Zheng; Ying-Ren Gao; Min-Xia Wu; Fang-Hong Gao; Hong-Zhang Wang; Kun Liu; Lin Yan (Biochemical Genetics, 2026)

Optoelectronic synaptic transistor array based on CsPbBr3/grating-patterned IDTBT heterojunctions for neuromorphic visual fatigue sensing - Jiajie Hong; Zhiqian Wei; Zunxian Yang; Yue Chen; Luxi Yuan; Shangwei Ye; Xudong Jiang; Yuting Bai; Benfang Liu; Zhiyu Yuan; Wenxin Zhang; Jie Li; et al. (Chemical Engineering Journal, 2026)

Corrigendum to “In vitro/vivo evaluation of novel mitochondrial targeting charge-reversal polysaccharide-based antitumor nanoparticle” [Carbohydrate Polymers Volume 234 (2020) 115930] - Lei Fang; Hua Lin; Zhenfeng Wu; Zhen Wang; Xinxin Fan; Ziting Cheng; Xiaoya Hou; Daquan Chen (Carbohydrate Polymers, 2026)

IoT-based automated monitoring and assessment of tea shoot density using canopy imaging - Hsin-Cheng Chen; Shih-Fang Chen; Shiou-Ruei Lin; Ta-Te Lin (Computers and Electronics in Agriculture, 2026)

Ultrasensitive electrochemiluminescence aptasensor for heparin-binding protein based on hybridization chain reaction (HCR) amplification and magnetic enrichment - Mengxin Cheng; Wanxin Xu; Yingying Cao; Yue Lin; Shenghang Zhang; Fang Luo; Bin Qiu; Zhenyu Lin (Analytica Chimica Acta, 2026)

Integrating biodiversity hotspots, ecological gradients, and ecosystem services for transboundary conservation in the Gaoligong Mountains - Zhongde Huang; Qiying Wang; Jie Wang; Zhou Fang; Lin Wang; Maroof Ali; Zhangqian Yang; Haoran Chen; Shi Xue; Qin Zhou; Changgao Cheng; Feiling Yang; et al. (Conservation Biology, 2026)
Expanding transboundary protected areas is crucial to biodiversity conservation and maintenance of ecosystem services. Quantifying border gradients of species richness is essential to aligning ecological and management boundaries to enable the gradual integration of biodiversity hotspots in conservation strategies that include cross‐border areas that buffer the effects of extensive infrastructure. For the China–Myanmar border region (Gaoligong Mountains), we developed a conservation plan based on threatened species, ecosystem services, border gradient characteristics (i.e., spatial changes in ecological variables with increasing distance from a boundary), and ecological connectivity of protected areas. Although 20.2% of existing protected areas were in the north, 27.7% of identified priority conservation areas were outside these protected areas and only 2.93% were protected. Threatened plant and animal richness exhibited a positive spatial correlation (coefficient = 0.12), but their richness hotspots were spatially mismatched. The richness of threatened species was positively correlated with carbon storage and soil retention, but negatively correlated with water retention. In contrast, threatened animal diversity showed the opposite pattern. Threatened species richness decreased as distance from the border increased (strong linear relationship, R 2 = 0.95 for plants and 0.59 for animals). Based on our results, we propose an ecological gradient–based conservation strategy that prioritizes areas where the richness of threatened species overlaps in the central and southern regions and that protects biodiversity hotspots and creates corridors. The framework is applicable to other transboundary regions and supports global biodiversity conventions.

Key factors affecting heavy metal contamination of mangrove sediments in the Zhangjiang Estuary: Implications for environmental management - Zheng Zhang; Lianzhi Zhong; Cheng Luo; Ting Fang; Lei Wang; Bin Yan; Jinpeng Wang; Xiuwen Ren; Yan Lin (Marine Pollution Bulletin, 2026)

Low-cholesterol egg yolk lipids alleviated the development of atherosclerosis in ApoE −/− mice by regulating bile acid metabolism and gut microbiota - Le Cheng; Ming Zhang; Fang Wu; Jianguo Dong; Yifei Wang; Lin Dong; Yumeng Ma; Chenyan Zheng; Zihan Wang; Yixuan Li; Ran Wang; Fazheng Ren; et al. (Food Research International, 2026)

Disentangling seasonal dynamics and transboundary transport of PAHs in a coastal monsoon city - Haolong Zhang; Zheng Zhang; Wenhui Lin; Guohui Lin; Cheng Luo; Ting Fang; Nemin Luo; Minggang Cai; Lei Wang; Bin Yan; Yan Lin (Atmospheric Research, 2026)

Functional characterization of PsnErf1b in regulating salt stress tolerance in poplar - Zihan Cheng; Xinyu He; Xinyue Tu; Haiyan Fang; Lin Liu; Tingbo Jiang; Xuemei Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

STAT3 Signaling Mediates Agomelatine Restoration of Prefrontal Cortex Synaptic Plasticity in Chronic Social Defeat Stress Mice - Chi-Wei Lee; Han-Fang Wu; Hsin-Ju Yen; Lun-De Liao; Wei-Chang Mao; Hsun-Shuo Chang; Yih-Fung Chen; Chia-Hsien Lin; Cheng-Ta Li; Hui-Ching Lin (Molecular Neurobiology, 2026)
Major depressive disorder (MDD) is a major public health issue worldwide. It not only causes an increased socio-economic burden, but also negatively affects personal lives. It has been shown that depression leads to impairments in synaptic plasticity, such as impaired long-term potentiation (LTP) in the prefrontal cortex (PFC). A recent study reported that administration of agomelatine, a melatonin receptor agonist and 5-hydroxytryptamine (5-HT) 2C antagonist, which may be involved in synaptic functions, for 1 week has a rapid antidepressive effect. Moreover, the mechanism of Glycogen synthase kinase 3β (GSK3β), regulated by signal transducer and activator of transcription 3 (STAT3), may play an important role in the synapse-related pathological mechanisms of depression. Hence, we used chronic social defeat stress (CSDS) as an animal model of depression, to investigate whether synaptic plasticity impairment in depression, improved by agomelatine, is mediated through the STAT3 mechanism. The results showed that depressive-like behaviors were reversed after 1 week of agomelatine treatment. Moreover, the impairment of LTP and alteration of spine density were reversed by agomelatine in the PFC. We further applied AG490, an inhibitor of STAT3, to demonstrate that the therapeutic mechanism of agomelatine improves synaptic plasticity through STAT3-regulated phosphorylation of GSK3β. Taken together, these results demonstrated that STAT3-regulated downstream molecules are potential therapeutic targets for the rapid action of antidepressants.

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Impact of fluctuations in influent quality on aerobic sludge granulation and nitrogen removal performance: Insights from extracellular polymeric substances and microbial community perspectives - Cheng Ding; Shiting Sun; Dexin Lin; Shuai Wang; Jixiang Yang; Jinsong Guo; Fang Fang (Journal of Environmental Chemical Engineering, 2025)

Hydrogeochemical characteristics and the monitoring from 2020 to 2023 of hot spring waters in Tatun Volcanic Group, Taiwan - Ju-lien Pi; Hsueh-Yu Lu; Hsiao-Fen Lee; Hung-Chun Chao; Chen-Feng You; Tsung-Ren Peng; Raymond Patrick R. Maximo; Chia-Tai Wu; Ya-Wen Wu; Chung Fang; Cheng-Horng Lin (Journal of Asian Earth Sciences, 2025)

Advances in the research on phenolic acids and flavonoids in vinegar: Sources, formation and degradation mechanisms, and functional properties - Cheng-Hao Jin; Yong-Zhu Zhang; Feng-Hua Wu; Chang-Ling Wu; Peng Wang; Wei Feng; Lin-Mei Liang; Wei-Jiang Xu; Xiao-Tao Sun; Xing-Quan Liu; Guan-Yu Fang (Food Research International, 2025)

HFPO-TA induces liver damage and ferroptosis in zebrafish by disrupting iron metabolism homeostasis - Lin Cheng; Zhonghua Fan; Yu Zhang; Xu Fang; Yuanyuan Wu; Hongru Liu; Lanxi Ye; Li Wang; Hui Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Alkylammonium ligands-driven perovskite lattice engineering for white perovskite nanocrystals single emitters - Jean-Sébastien Bénas; Zhen-Li Yan; Wei-Cheng Chen; Chu-Chen Chueh; Jing-Yan Wu; Wei-Wen Chen; Fang-Cheng Liang; Erdi Akman; Yu-Jung Lu; Yen-Yu Wang; Ja-Hon Lin; Ye Zhou; et al. (Chemical Engineering Journal, 2025)

Serum cortisol and AdipoR2 rs12342 were involved in the correlation between stress and serum cholesterol in a gender-specific manner - Yi Lin Shen; Qi Wei Guo; Xue Cheng Li; Ke Xin Jia; Jun Yi Liu; Yan Zhi Yi; Jun Tao Ren; Jia Jing Cai; Guo Ming Su; Jia Lin; Ding Zhi Fang (Metabolic Brain Disease, 2025)

Analysis of cellular and gene therapy product reviews in the United States - Cheng-Fang Weng; Jhe-Yuan Dong; Shiuan-Fei Lin; Ai-Lei Jiang; Yu-Li Cheng; Lin-Chau Chang (Regulatory Toxicology and Pharmacology, 2025)

Protective effects of microalgal macular pigment on diabetic retinopathy upon blue light irradiation induced oxidative stress, inflammation, and MAPK pathways - Meng-Wei Lin; Cheng-Han Lin; Wei-Hong Chiu; Hui-Fang Chang; Wai-Man Cheang; Chien-Chun Chang; Vivian C.H. Wu; Chih-Sheng Lin; Chiu-Mei Kuo (Food Research International, 2025)

Isolation of largemouth bass virus (LMBV) and dominant immunogenic epitope screening of the major capsid protein of LMBV - Jie Leng; Ling-Yun Lin; Yun-Yao Tu; Cheng-Ke Zhu; Qun Lu; Ming-Ji Lv; Tao He; Jian-Yong Hu; Zhao-Fang Han; Song Zhu (Fish & Shellfish Immunology, 2025)

Association of compound exposure to heat wave and ozone pollution with cause-specific cardiopulmonary mortality: A space-time-stratified case-crossover study - Kang Ma; Fengman Fang; Yuesheng Lin; Fei Tong; Cheng He; Youru Yao; Jingli Zhu; Huadong Wang; Xiuya Xing; Feiyan Zhang; Ruoxi Li (Environmental Research, 2025)

Corrigendum to “Nanoplatforms derived from iron dextran combined with ascorbic acid for enhanced photothermal-chemodynamic therapy of tumors” [Chem. Eng. J. 496 (2024) 154044] - Bin Zhang; Xiao-Lin Hou; Xiao-Ting Xie; Lin-Fang Tan; Meng Guan; Dong-Hui Zhao; Sui Zhou; Kai Cheng; Jin-Xuan Fan; Bo Liu (Chemical Engineering Journal, 2025)

Preparation of antibacterial CO2-based polycarbonate hydrogels with dual cross-linkages for co-loading of antibiotics and hypoglycemic agents and their applications on diabetic wound dressings - Zheng-Ian Lin; Tzu-Hsien Tsai; Guan-Lin Liu; Chih-Yuan Hsu; Siang-Ming Tsai; Yi-Ping Fang; Wing-Cheung Law; Han-Lin Tsai; Jia-Ying Tsai; Hsuan-Ying Chen; Bao-Tsan Ko; Pei-Wen Cheng; et al. (Chemical Engineering Journal, 2025)

HFPO-TA exposure triggers hepatomegaly and lipid peroxidation via Nrf2/keap1 antioxidant dysregulation and ferroptosis activation in the liver - Xu Fang; Zhonghua Fan; Mengjiao Li; Zhi Li; Lin Cheng; Yuanyuan Wu; Li Wang; Hui Liu (Chemico-Biological Interactions, 2025)

Human adenovirus in Taiwan, 2019–2023 - Su-Lin Yang; Wan-Ju Tsai; Chung-Hao Li; Yu-Hsin Cheng; Shu-Wei Lin; Ming-Tsan Liu; Fang-Tzy Wu (Archives of Virology, 2025)

Dynamic in situ counting of farmed Holothurians based on improved YOLOv8s-ByteTrack - Ke-Xin Liu; Fang Wang; Sheng-Cheng Hong; Jun-Yi Wang; Xin-Yu Zheng; Yuan-Shan Lin (Aquaculture International, 2025)

The mobility, host, and co-occurrence of antibiotic resistance genes in multi-type pig manure-soil systems: Metagenome assembly analysis - Xiangyue Xu; Xvdong Lin; Mengya Fang; Meixia Huo; Ziyan Kou; Wenjin Ma; Xiaoqian Li; Qiuqi Cheng; Hanyu Wang; Lingli Huang (Journal of Environmental Management, 2025)

Interfacial engineering meets process optimization: Highly stable silicon-graphite anodes via pre-calendering polyvinylidene difluoride-MgO coatings - Chu-Chun Lin; Cheng-Che Chien; Yu-Ting Weng; Chia-Chen Fang; Nae-Lih Wu; Rainer Adelung; Mozaffar Abdollahifar; Ryo Takata; Carlos Eduardo Alarcón-Suesca; Franz Schmidt (Chemical Engineering Journal, 2025)

Short-term deep-sea cage culture of Trachinotus ovatus increases mobility of antibiotic-resistance genes - Haikun Zhang; Yingchun Han; Suyun Fang; Shenghui Zhang; Manman Cheng; Xingyue Lin; Xiaoke Hu (Aquacultural Engineering, 2025)

System temperature prediction and verification of all-sky electrostatic analyzer on the lunar surface - Tsung-Pin Hung; Chih-Yu Chiang; Tzu-Fang Chang; Zhao-Yu Huang; Yu-Rong Cheng; Sheng-Cheng Tsai; Tzu-En Yen; Jih-Run Tsai; Shin-Fa Lin (Advances in Space Research, 2025)

Spatial heterogeneity in the joint effect of heat wave and ozone pollution on mortality at the township-level in China - Kang Ma; Fengman Fang; Yuesheng Lin; Fei Tong; Cheng He; Youru Yao; Jingli Zhu; Huadong Wang; Xiuya Xing (Sustainable Cities and Society, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Multi-omics analysis reveals BPF exposure causes hepatic glucose and lipid metabolism disorder in rats by disrupting energy homeostasis - Zhi Li; Yuanyuan Wu; Mingqing Qian; Bingya Zhang; Xinxin Deng; Penghui Mao; Zhonghua Fan; Xu Fang; Lin Cheng; Xuan Liu; Li Wang; Hui Liu (Toxicology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Sequential delivery of anti-inflammatory and anti-scar drugs by Rg3 liposome-embedded thiolated chitosan hydrogel eye drops for corneal alkali burn - Huan Tang; Xinnan Li; Chunmei Li; Wenhao Shen; Lin Jin; Yumeng Zhou; Wenna Jiao; Lijun Zhang; Fang Cheng (Carbohydrate Polymers, 2025)

Exploring Lumbar Ligamentum Flavum, Disc Height and Foraminal Height Variations Across Different Postures: A Cadaveric Computed Tomography Investigation - Yuan-Fu Liu; Nozomu Inoue; Yu-Hua Dean Fang; Jing-Yao Wang; Alejandro A. Espinoza Orías; Chao-Jui Chang; Cheng-Li Lin (Journal of Medical and Biological Engineering, 2025)

Impact of ethanol-gasoline implementation on regulated and unregulated emissions from Euro 3–5 standard vehicles over the WLTP driving cycle - Syu-Ruei Jhang; Guor-Cheng Fang; Way Lee Cheng; Kun-Yeh Lee; Yuan-Chung Lin (Environmental Monitoring and Assessment, 2025)

Fire ants exhibit self-medication but lack preventive behavioral immunity against a viral pathogen - Fang-Ling Chloe Liu; Wei-Jiun Lin; Liam McMillan; Chin-Cheng Scotty Yang (Journal of Invertebrate Pathology, 2025)

Liquid–liquid phase separation in normal hematopoiesis and hematological diseases - Lexuan Lin; Fang He; Xu Jin; Xiaoru Zhang; Yue Li; Di Wang; Jingwei Wang; Lingyue Zheng; Haoze Song; Xu Zhu; Qimei Cheng; Yitong Zhao; et al. (Cell and Tissue Research, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Spatial patterns of essential fish habitats in the western Taiwan coast - Yu-Jia Lin; Chien-Cheng Lai; Hsu-Sen Chen; Tsu-Chun Chen; Kuo-Shu Chen; Norhafiz Hanafi; Pei-Jie Meng; Ying-Chin Fang; Chiee-Young Chen; Hsin-Ming Yen; Meng-Hsien Chen (Estuarine, Coastal and Shelf Science, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

BTEX exposure and metabolite levels in Taiwan schoolchildren near petrochemical areas - Wei-shan Chin; Ching-chun Huang; Yu-cheng Chen; Jing-fang Hsu; Chih-Da Wu; Pinpin Lin; Pau-chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

Metabolic profiling and evaluation of antioxidant and anti-inflammatory properties of Apis cerana cerana Honey from Sansha City, Hainan Province, China - Jiao Wu; Xiang-Tan Xu; Cheng Xing; Xin-Bao Hao; Xing-Yue Fang; Zhi-Hao Xie; Shan Zhao; Jing-Lin Gao; Lu Xu; Shi-Jie Wang (Food Chemistry, 2025)

Enhancing color conversion of perovskite quantum dot-based micro-light-emitting diodes via electrochemical etching and flow chemistry system - Wen-Tse Huang; Yen-Huei Lin; Po-Yi Tu; Loan Thi Ngo; Wei-Cheng Chen; Kai-Ling Liang; Yen-Hsiang Fang; Chaochin Su; Ru-Shi Liu (Chemical Engineering Journal, 2025)

Specifically targeted antimicrobial cyclic peptide to staphylococcal protein A for the treatment of S. aureus infection - Xiao-Ling Lei; Yong Li; Xue-Ting Cheng; Jie Zhuang; Fang Zhang; Xiao-Ting Xie; Lin-Fang Tan; Jin-Xuan Fan; Yuan-Di Zhao; Chuan-Liu Wu; Kai Cheng (Chemical Engineering Journal, 2025)

Epidemiology and pathogenesis of the link between rheumatoid arthritis and periodontitis - Huiya Fang; Jin Lin; Yiwu Qiu; Zijian Cheng; Weiqian Chen (Journal of Zhejiang University-SCIENCE B, 2025)

Development of a rat airway organoids model for studying chronic obstructive pulmonary disease - Chuanlai Yang; Hongwei Yang; Yangling Xian; Nanyi Liu; Haoyin Tan; Zirui Ren; Yanzhen Lin; Huan Zhao; Changjian Fang; Kang Yu; Dequan Pan; Yali Zhang; et al. (Tissue and Cell, 2025)

Development and Application of Cavity-based Absorption Spectroscopy in Atmospheric Chemistry: Recent Progress - Weixiong Zhao; Nana Yang; Renzhi Hu; Bo Fang; Jiacheng Zhou; Chuan Lin; Feihu Cheng; Pinhua Xie; Weijun Zhang (Advances in Atmospheric Sciences, 2025)
Atmospheric chemistry research and atmospheric measurement techniques have mutually promoted each other and developed rapidly in China in recent years. Cavity-based absorption spectroscopy, which uses a high-finesse cavity to achieve very long absorption path-length, thereby achieving ultra-high detection sensitivity, plays an extremely important role in atmospheric chemistry research. Based on the Beer–Lambert law, this technology has the unique advantages of being non-destructive, chemical-free, and highly selective. It does not require any sample preparation and can quantitatively analyze atmospheric trace gases in real time and in situ. In this paper, we review the following: (1) key technological advances in different cavity-based absorption spectroscopy techniques, including cavity ring-down spectroscopy, cavity-enhanced absorption spectroscopy, cavity attenuated phase shift spectroscopy, and their extensions; and (2) applications of these techniques in the detection of atmospheric reactive species, such as total peroxy radical, formaldehyde, and reactive nitrogen (e.g., NO x , HONO, peroxy nitrates, and alkyl nitrates). The review systematically introduces cavity-based absorption spectroscopy techniques and their applications in atmospheric chemistry, which will help promote further communication and cooperation in the fields of laser spectroscopy and atmospheric chemistry.

The herbicide 2,4-dichlorophenoxyacetic acid induces pancreatic β-cell death via oxidative stress-activated AMPKα signal downstream-regulated apoptotic pathway - Ken-An Lin; Chin-Chuan Su; Kuan-I Lee; Shing-Hwa Liu; Kai-Min Fang; Chih-Hsin Tang; Wei-Cheng Lia; Chun-Ying Kuo; Kai-Chih Chang; Chun-Fa Huang; Ya-Wen Chen; Ching-Yao Yang (Toxicology Letters, 2025)

Nonlinear flutter critical state prediction for a bridge girder based on instantaneous power balance principle - Yue Cheng; Genshen Fang; Wei Cui; Yongle Li; Lin Zhao (Engineering Structures, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

A new diterpenoid alkaloid from the Aconitum scaposum - Cheng-En Fu; Gui-Fang Li; Guo-Qing Sun; Shuai Huang; Lin Chen; Xian-Li Zhou (Phytochemistry Letters, 2025)

Effect of vacuum frying on the structure and bioactivity of proanthocyanidins in Chinese quince (Chaenomeles sinensis Koehne) fruit - Yu Lou; Xu Fang; Zi-Cheng Yang; Jia-Lin Fei; Yu-Ru Feng; Zhao Qin; Hua-Min Liu; Yu-Xiang Ma; Xue-De Wang (Food Chemistry, 2025)

Peroxisome-inspired T4 phage hybrid enzyme nanoreactors for photodynamic therapy of breast cancer - Xiao-Lin Hou; Lin-Fang Tan; Xiao-Ting Xie; Bin Zhang; Qiong Wang; Kai Cheng; Jin-Xuan Fan; Tian-Cai Liu; Bo Liu (Chemical Engineering Journal, 2025)

Analysis of serotype distribution and characteristics of nonhemolytic and nonpigmented strains among group B Streptococcus isolates in a southern Taiwan local hospital - Hui-Fang Cheng; Zhe-Yu Kuo; Ching-Chiang Lin; Ho-Feng Chen; Horng-Ren Lo; Huey-Wen Shyu; Yi-Fen Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Tetrabromobisphenol A induced p38-MAPK/AMPKα activation downstream-triggered CHOP signal contributing to neuronal apoptosis and death - Jui-Ming Liu; Shing-Hwa Liu; Shih-Chang Fu; Wei-Cheng Lai; Kai-Min Fang; Ken-An Lin; Jun-An Ke; Chun-Ying Kuo; Chin-Chuan Su; Ya-Wen Chen (Toxicology, 2025)

Effective removal of Pb from industrial wastewater: A new approach to remove Pb from wastewater based on engineered yeast - Hao Luo; Zheng Su; Yang Liu; Dong-Fang Yuan; Rui Wang; Yu-Hang Ning; Dong-Jiao Zhang; Xian-Ke Chen; Zhao-Bao Wang; Xue-Yan Gao; Yue-Chao Zhang; Guang Cheng; et al. (Journal of Hazardous Materials, 2025)

Elastomer foam templated three dimensional hybrid hydrogels for heterogeneously integrated stretchable electronics - Changqing Qin; Qian Wang; Ting Fang; Lin Wang; Cheng Yang; Yong Lin; Chong Bai; Wenqiang He; Likang Ding; Jinheng Zhang; Dongchan Li; Desheng Kong (Chemical Engineering Journal, 2025)

Application of seismically derived tilt signals to characterize groundwater flow regimes: An example from a constant-rate pumping test in Taiwan - Chu-Fang Yang; Wu-Cheng Chi; Chien-Chung Ke; Chin-Jen Lin (Journal of Hydrology, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

Enhancing real-time PM2.5 forecasts: A hybrid approach of WRF-CMAQ model and CNN algorithm - Yi-Ju Lee; Fang-Yi Cheng; Hsiao-Chen Chien; Yuan-Chien Lin; Min-Te Sun (Atmospheric Environment, 2024)

Effects of alligator weed invasion on wetlands in protected areas: A case study of Lishui Jiulong National Wetland Park - Xiang-Hua Fang; Xuan-Ming Chen; Ri-Lin Liu; Si-Hai Zhang; Jun-Qin Gao; Bi-Cheng Dong; Fei-Hai Yu (Science of The Total Environment, 2024)

Copper-based photocatalysts with natural organic ligands for efficient removal of tetracycline under visible light - Shouxin Zhu; Can Sun; Zhexiao Zhu; Jingyi Qu; Zijie Fang; Yangben Chen; Jiahui Lin; Xiaolu Xu; Miaoyan Cheng; Min Jiang; Hui Zheng (Journal of Environmental Management, 2024)

Spray-on electronic tattoos with MXene and liquid metal nanocomposites - Lin Wang; Yong Lin; Cheng Yang; Qian Wang; Ting Fang; Chong Bai; Jianhui Wang; Desheng Kong (Chemical Engineering Journal, 2024)

Environmental exposure patterns to 94 current-use pesticides in women of reproductive age who are preparing for pregnancy - Tian Tian; Fang Liu; Yu Fu; Junjie Ao; Shujian Lin; Qianhui Cheng; Kalbinur Kayim; Fei Kong; Linlin Wang; Xiaoyu Long; Yuanyuan Wang; Jie Qiao (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

An unusual winter bloom of dinoflagellates with notable damage to kelp cultivation around Shandong peninsula, China - Hui-Xia Geng; Fan-Zhou Kong; Jin-Xiu Wang; Qing-Chun Zhang; Fang Li; Xin Hong; Min-Jie Song; Ziru Lian; Yu-Lin Cai; Ren-Cheng Yu (Marine Environmental Research, 2024)

Colorimetric sensing based on silver nanoparticle-functionalized copper porphyrin nanozyme for glyphosate - Li-Hong Yu; Rui Jiang; Cheng-Lin Yang; Yue-Hong Pang; Xiao-Fang Shen (Food Bioscience, 2024)

Inflammatory microenvironment-responsive “double-insurance” nanoreactors for accurate sonodynamic-chemodynamic therapy of rheumatoid arthritis - Sui Zhou; Meng-Wen Ma; Shao-Zhe Cai; Kai-Lin He; Lin-Fang Tan; Kai Cheng; Jin-Xuan Fan; Ling-Li Dong; Bo Liu (Chemical Engineering Journal, 2024)

Measuring Spatial Radiation Dose Distribution During Abdominal Computed Tomography Scanning with Optically Stimulated Luminescence Dosimeters - Wen-Chuan Chang; Tian-Yu Shih; Pei-Ren Fang; Cheng-Hsun Lin (Journal of Medical and Biological Engineering, 2024)
Purpose As the proportion of medical radiation exposure increases, the exposure dose has received increasing attention. When performing interventional radiological diagnosis, examiners are often exposed to radiation. Therefore, patients and medical personnel are exposed to higher amounts of radiation dose. Accordingly, we used optically stimulated luminescence dosimeters (OSLDs) to measure the ambient air kerma during abdominal CT scanning to observe the spatial distribution of the doses. Methods An abdominal CT scan under a voltage of 120 kVp was performed, and OSLDs were used for the measurement. The measurement range extended from the examination couch that serves as the center point to the walls and was divided into four areas. The OSLD measurements were undertaken at three different heights (i.e., 85, 140, and 150 cm from the floor) for spatial dose detection. The OSLDs were fixed up to lines at the three height levels. Each dosimetry point was 50 cm apart. In addition, the surface incident doses of the prosthesis's mammary gland, liver, and gonad were estimated. Results According to the spatial dose distribution at the three different heights, the maximum dose and minimum dose in front of the bore were 0.194 ± 0.008 and 0.006 ± 0.001 mGy, respectively; 2 m away from the bore, the dose reduced to 9% of the maximum dose. The surface incident doses of the mammary gland, liver, and gonad were 1.321 ± 0.121, 13.083 ± 0.642, and 13.441 ± 0.658 mGy, respectively. Conclusion The spatial dose distribution revealed that the dose was the highest at the height of 140 cm and in front of the bore. The dose on the left side was higher than that on the right side. In addition, the dose was inversely proportional to the square of the distance. If the examiners must perform interventional radiological diagnosis during CT scanning, they should put on radiation protection equipment and stand behind the bore to minimize the radiation exposure.

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Nanoplatforms derived from iron dextran combined with ascorbic acid for enhanced photothermal-chemodynamic therapy of tumors - Bin Zhang; Xiao-Lin Hou; Xiao-Ting Xie; Lin-Fang Tan; Meng Guan; Dong-Hui Zhao; Sui Zhou; Kai Cheng; Jin-Xuan Fan; Bo Liu (Chemical Engineering Journal, 2024)

Enhancing interfacial compatibility and ionic transportation kinetics in lithium-rich manganese oxide via magnetron sputtering conformal coating with amorphous LiPON - Yue Chen; Yulin Huang; Chenxi Fang; Pengcheng Wang; Houlin Cheng; Guiying Zhao; Yingbin Lin; Zhigao Huang; Jiaxin Li (Chemical Engineering Journal, 2024)

The application of a high-density street-level air temperature observation network (HiSAN): Spatial and temporal variations of thermal and wind condition in different climatic condition types - Yu-Cheng Chen; Kai-Shan Hou; Yu-Jie Liao; Tsuyoshi Honjo; Fang-Yi Cheng; Tzu-Ping Lin (Sustainable Cities and Society, 2024)

An emerging antibacterial nanovaccine for enhanced chemotherapy by selectively eliminating tumor-colonizing bacteria - Linfu Chen; Zheyu Kang; Jingjing Shen; Rui Zhao; Yu Miao; Lin Zhang; Zixuan Zheng; Zhemin Zhang; Nanhui Liu; Cheng Wang; Huapan Fang; Jun Zhou; et al. (Science Bulletin, 2024)

Dual-Targeting EGCG/NO-Supplying protein assembled nanoparticles with Multi-Synergistic effects against atherosclerosis - Chi Lin; Tsai-Mu Cheng; Yun-Chun Liu; Fang-Yu Hsu; Chun-Ming Shih; Min-Lang Tsai; Chun-Che Shih; Fwu-Long Mi (Chemical Engineering Journal, 2024)

Awakening dumb Mn2+ mechanoluminescence site to achieve force, temperature and time-domain induced color tuning via trap-assisted energy transfer - Jiaqi Ou; Shuangqiang Fang; Haoliang Cheng; Dongjie Han; Qiangqiang Zhu; Yue Zhai; He Lin; Jiali Yu; Renjie Xu; RongJun Xie; Le Wang (Chemical Engineering Journal, 2024)

Influences on medical app adoption by patients: the unified theory of acceptance and use of technology model and the moderating effects of technology readiness - Yung-Zung Chang; Chen-Wei Yu; Cheng-Min Chao; Fang-Chen Lin (The Social Science Journal, 2024)

Tuning multiple enzyme-like activities by metal doping for identification and quantitation of antioxidants in cosmetics - Sheng-Tao Wu; Hui-Qi Su; Kai-Lin Shen; Ying Li; Yi Ge; Xiu-Fang Cheng; Chang-Ming Nie; Cong-Hui Wang; Ying-Wu Lin (Chemical Engineering Journal, 2024)

Erratum to: Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

The effects of repeated freezing and thawing on bovine sperm morphometry and function - Chang-Guo Min; Xin Ma; Yu-Chan Wang; Cheng-Kun Zhong; Chong-shan Yuan; Kai-Yan Zhang; Cheng-Lin Zhan; Sheng-Kui Hou; Xin-Hai Wang; Jun Wang; Jing Zhao; Yi Fang; et al. (Cryobiology, 2024)

Chemical constituents of the deep-sea-derived fungus Trichoderma simmonsii ZEN3 and their chemotaxonomic significance - Li-Fang Liu; Yuan Wang; Rong Chao; Lin Xu; Zheng-Biao Zou; Kai Zhang; Ming-Min Xie; Xian-Qiang Chen; Cheng-Hai Gao; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

An Automatic Approach of Video-Based Landmark Detection and Movement Analysis for Assessing Symptoms of Bradykinesia in Parkinson’s Disease - Ching-Fang Chien; Chen-Sen Ouyang; Yi-Hung Chiu; Lung-Chang Lin; Rei-Cheng Yang; Yang-Pei Chang; San-Yuan Wang; Li-Min Liou (Journal of Medical and Biological Engineering, 2024)

Tumor necrosis factor receptor-associated factor 5 protects against intimal hyperplasia by regulation of macrophage polarization via directly targeting PPARγ - Wen-Lin Cheng; Sheng-ping Chao; Fang Zhao; Huan-Huan Cai; Ziyue Zeng; Jian-Lei Cao; Zhili Jin; Ke-Qiong Deng; Xiaorong Hu; Hairong Wang; Zhibing Lu (Inflammation Research, 2024)

Algae-bacteria consortia promotes the cell growth of marine microalgae Phaeodactylum tricornutum and Chrysotila roscoffensis - Jiaqi Fang; Yan Sun; Zhujun Zhu; Jian Li; Pengfei Cheng; Spiros N. Agathos; Yuanyuan Fu; Lin Zhang; Chengxu Zhou; Jichang Han (Algal Research, 2024)

Methionine redox regulation of actin-interacting proteins primarily governs antioxidative signaling and response to the salvianolic acid B treatment in EA.hy926 cells - Ai-Cheng Wang; Xiao-Ming Qi; Qing-Fang Li; Yi-Jia Feng; Yuan-Lin Zhang; Hui-Zhi Wei; Jin-Shan Li; Yuan-Biao Qiao; Qing-Shan Li (Toxicology and Applied Pharmacology, 2024)

CO2 enrichment and excess nitrogen supply synergistically increase toxicity of marine dinoflagellate Alexandrium minutum - Fang Li; Lin Guo; Junhui Chen; Ziru Lian; Ren-Cheng Yu (Journal of Hazardous Materials, 2024)

Highly sensitive biosensor for specific miRNA detection based on cascade signal amplification and magnetic electrochemiluminescence nanoparticles - Jiawen Li; Cheng Chen; Fang Luo; Zhenyu Lin; Jian Wang; Aiwen Huang; Ying Sun; Bin Qiu (Analytica Chimica Acta, 2024)

Oncogenic and immunological roles of RACGAP1 in pan-cancer and its potential value in nasopharyngeal carcinoma - Cheng-shan Zheng; Wei-mei Huang; Hong-mei Xia; Jing-lin Mi; Yuan-qing Li; Hui-qing Liang; Li Zhou; Zhou-xue Lu; Fang Wu (Apoptosis, 2024)

Ozone containment through selective mitigation measures on precursors of volatile organic compounds - Sheng-Po Chen; Wen-Tzu Liu; Fang-Yi Cheng; Chieh-Heng Wang; Shih-Ming Huang; Jia-Lin Wang (Science of The Total Environment, 2024)

Transient ground bulge derived from a dense broadband seismic array during an aquifer step-drawdown pumping test - Wu-Cheng Chi; Chu-Fang Yang; Sebastian Wege; Chin-Jen Lin; Chien-Chung Ke (Journal of Hydrology, 2024)

A colorimetric sensing platform with smartphone for organophosphorus pesticides detection based on PANI-MnO2 nanozyme - Cheng-Lin Yang; Li-Hong Yu; Yue-Hong Pang; Xiao-Fang Shen (Analytica Chimica Acta, 2024)

Response of distributions and emissions of summer biogenic sulfur in the Pacific Arctic to enhanced Pacific Water inflow - Cheng‐Xuan Li; Bao‐Dong Wang; Kan Chen; Gui‐Peng Yang; Jian‐Fang Chen; Li‐Na Lin; Zi‐Cheng Wang (Limnology and Oceanography, 2024)
The inflow of warm and nutrient‐rich Pacific Water (PW) through the Bering Strait into the Arctic Ocean is likely to have far‐reaching consequences for the ecosystem and biogenic sulfur cycle in the Earth's sensitive subarctic–arctic region of the Pacific sector, even impacting climate change under global warming scenarios. We performed a detailed biogeochemical study of summer biogenic sulfur cycling from cold (2012) to warm (2014) years in the Bering Strait and the Chukchi Sea, so as to highlight the importance of enhanced Pacific inflow in driving dimethylsulfide (DMS) variability. In the Bering Strait, the enhanced Pacific inflow led to the vertical expansion of the eastern high‐DMS regions due to the vertical extension of Alaska Coastal Water, and the horizontal expansion of the western surface high‐DMS regions due to the westward intrusion of Bering Shelf Water. The enhanced extension of PW potentially stimulated seawater warming, the northward retreat of the ice edge, and the enlargement of sea ice‐free areas in the Chukchi Sea. The northern ice melting zone at 71°N with a bloom of phytoplankton was an area of locally high dimethylsulfoniopropionate concentrations and slow DMS consumption in 2012. A hotspot for dimethylated sulfur compound concentrations and DMS sea–air flux occurred in the convergence region near 67.7°N during 2014, due to enhanced mixing caused by increased Bering Sea Water. Owing to the increased advection of PW during 2012–2014, surface DMS and its emission to the atmosphere increased sharply by threefold in the Chukchi Sea.

Active packaging incorporating chitosan, casein phosphopeptide, and plasmonic modification to maintain quality and regulate the respiration rate of fresh-cut Pyrus serotina Rehder during storage - Chao-Kai Chang; Fang-Yu Lin; Sheng-Yen Tsai; Mohsen Gavahian; Kuan-Chen Cheng; Chih-Yao Hou; Min-Hung Chen; Shella Permatasari Santoso; Chang-Wei Hsieh (Food Packaging and Shelf Life, 2023)

Association of mono-2-ethylhexyl phthalate with adverse outcomes in chronic hemodialysis patients - Chia-Lin Wu; Yu-Wei Fang; Yi-Chou Hou; Kuo-Cheng Lu; Wen-Hsin Tsai; Ping-Hsun Lu; Tzong-Shyuan Lee; Ko-Lin Kuo (Environmental Science and Pollution Research, 2023)
Phthalate exposure is widespread and has a global impact. Growing evidence shows that mono-2-ethylhexyl phthalate (MEHP) exposure has a negative impact on human health. However, whether MEHP exposure is associated with mortality and other adverse outcomes in hemodialysis patients remains unknown. This study prospectively enrolled 217 patients on maintenance hemodialysis from June 30, 2021, to August 16, 2022. Baseline serum MEHP, di-2-ethylhexyl phthalate (DEHP), and indoxyl sulfate (IS) concentrations were measured. Primary endpoints were all-cause mortality or composite adverse outcomes, including all-cause death plus hospitalization due to cardiovascular disease, heart failure, stroke, infection, or cancer. Serum MEHP concentrations were positively associated with DEHP but not indoxyl sulfate concentrations in hemodialysis patients. Additionally, serum MEHP concentrations were significantly and independently associated with all-cause mortality and composite adverse outcomes (adjusted hazard ratios [HRs], 1.04 and 1.03 per ng/mL, 95% confidence intervals [CIs], 1.01–1.07 and 1.00–1.05; p = 0.016 and 0.015, respectively). We found a cutoff value of MEHP for predicting both endpoints. Patients with serum MEHP concentrations of ≥ 41.8 ng/mL had much higher risks for all-cause mortality and composite adverse outcomes (adjusted HRs, 39.2 and 13; 95% CIs, 2.44–65.7 and 2.74–61.4; p = 0.011 and 0.001, respectively). MEHP exposure is significantly associated with higher risks for all-cause mortality and composite adverse outcomes. Hemodialysis patients with serum MEHP concentrations above 41.8 ng/mL had much poorer prognoses regarding both outcomes.

Heart valve-inspired self-lubricating anticoagulant surfaces - Yang Cheng; Zhiwei Yang; Xiaodan Gou; Qing Yang; Zichen Zhang; Shiyu Cui; Yuhua Ren; Lihong Fan; Haifeng Zhang; Zheng Fang; Yu Lu; Lin Kai; et al. (Chemical Engineering Journal, 2023)

Co-exposure to iron, copper, zinc, selenium and titanium is associated with the prevention of gastric precancerous lesions - Tingting Wang; Fang Xu; Xiao Lin; Yaning Lv; Xiaohui Zhang; Wenli Cheng; Li Wang; Min Wang; Meng Zhang; Tao Xia; Shiqing Qian; Min Tang; et al. (BioMetals, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

β-Cyclodextrin network crosslinked by novel phosphonium-based tetrakiscarboxylic acid derived from PH3 tail gas: Synthesis and application for rapid removal of organic dyes from wastewater - Yu-Lin Hong; Jian Sun; Xiu-Qin Fang; Qing-Wen Liu; Chang Wang; Cheng-Mei Liu (Carbohydrate Polymers, 2023)

Dynamic total factors’ environmental efficiency in European union countries - Ching-Cheng Lu; Yung-ho Chiu; I-Fang Lin; Tai-Yu Lin (Environment, Development and Sustainability, 2023)

Bidirectional crosstalk of the cAMP/ROS-dependent signaling pathways in inflammatory macrophage: An activation of formononetin - Lan-Fang Zhang; Xiao-Yan Zhang; Ai-Cheng Wang; Yi-Jia Feng; Xiao-Ming Qi; Yuan-Lin Zhang; Qing-Fang Li; Yuan-Biao Qiao; Qing-Shan Li (Toxicology and Applied Pharmacology, 2023)

Ammoniated straw incorporation increases maize grain yield while decreasing net greenhouse gas budget on the Loess Plateau, China - Jinchao Li; Yue Li; Zhipeng Yang; Yanxin Fang; Cheng Li; Yulong Shi; Nanping Lin; Qinge Dong; Kadambot H.M. Siddique; Hao Feng; Naijiang Wang (Agriculture, Ecosystems & Environment, 2023)

Plasma cell-free DNA promise monitoring and tissue injury assessment of COVID-19 - Xin Jin; Yanqun Wang; Jinjin Xu; Yimin Li; Fanjun Cheng; Yuxue Luo; Haibo Zhou; Shanwen Lin; Fei Xiao; Lu Zhang; Yu Lin; Zhaoyong Zhang; et al. (Molecular Genetics and Genomics, 2023)
Coronavirus 2019 (COVID-19) is a complex disease that affects billions of people worldwide. Currently, effective etiological treatment of COVID-19 is still lacking; COVID-19 also causes damages to various organs that affects therapeutics and mortality of the patients. Surveillance of the treatment responses and organ injury assessment of COVID-19 patients are of high clinical value. In this study, we investigated the characteristic fragmentation patterns and explored the potential in tissue injury assessment of plasma cell-free DNA in COVID-19 patients. Through recruitment of 37 COVID-19 patients, 32 controls and analysis of 208 blood samples upon diagnosis and during treatment, we report gross abnormalities in cfDNA of COVID-19 patients, including elevated GC content, altered molecule size and end motif patterns. More importantly, such cfDNA fragmentation characteristics reflect patient-specific physiological changes during treatment. Further analysis on cfDNA tissue-of-origin tracing reveals frequent tissue injuries in COVID-19 patients, which is supported by clinical diagnoses. Hence, our work demonstrates and extends the translational merit of cfDNA fragmentation pattern as valuable analyte for effective treatment monitoring, as well as tissue injury assessment in COVID-19.

Long-term DEHP/MEHP exposure promotes colorectal cancer stemness associated with glycosylation alterations - Pei-Chun Shih; Hsin-Pao Chen; Ching-Cheng Hsu; Chung-Hsien Lin; Chou-Yuan Ko; Chao-Wen Hsueh; Cheng-Yi Huang; Tian-Huei Chu; Cheng-Chun Wu; Yu-Cheng Ho; Ngoc Uyen Nhi Nguyen; Shih-Chung Huang; et al. (Environmental Pollution, 2023)

Insight into the effect of pyrolysis temperature on photoreactivity of biochar-derived dissolved organic matter: Impacts of aromaticity and carbonyl groups - Hanzhuo Luo; Eydhah Almatrafi; Wenjun Wang; Yang Yang; Danlian Huang; Weiping Xiong; Min Cheng; Chengyun Zhou; Yin Zhou; Qing Lin; Guoge Fang; Guangming Zeng; et al. (Science of The Total Environment, 2023)

High fructose-induced skeletal muscle insulin resistance could be alleviated by berberine via AMPD1 and ADSL - Juanjuan Cheng; Xingdong Ma; Guangtao Yan; Qiuxia Yu; Zhen Huang; Guoshu Lin; Mengyao Li; Fengkun Guan; Ziren Su; Fang Yan; Yuhong Liu; Qingfeng Xie (Food and Chemical Toxicology, 2023)

pH and non-enzymatic glucose response at ultra-low concentration using submicrochannel heterogeneous membrane - Yuan-Ju Tang; Kai Cheng; Lin-Fang Tan; Xiao-Ting Xie; Bin Zhang; Wen-Ming Su; Yuan-Di Zhao; Qiu-Ran Xu (Chemical Engineering Journal, 2023)

The eradication of biofilm for therapy of bacterial infected chronic wound based on pH-responsive micelle of antimicrobial peptide derived biodegradable microneedle patch - Xiao-Ling Lei; Kai Cheng; Yong Li; Zi-Tao Zhong; Xiao-Lin Hou; Lai-Bo Song; Fang Zhang; Jian-Hao Wang; Yuan-Di Zhao; Qiu-Ran Xu (Chemical Engineering Journal, 2023)

Paper-based analytical device coupled with Bi-MOF: Electric field amplification and fluorescence sensing of glyphosate - Chao-Qun Wan; Yue-Hong Pang; Qiu-Yu Yang; Cheng-Lin Yang; Xiao-Fang Shen (Analytica Chimica Acta, 2023)

Corrigendum to “Induction of core symptoms of autism spectrum disorders by in vivo CRISPR/Cas9-based gene editing in the brain of adolescent rhesus monkeys” [Sci. Bull. 66(9) (2021) 937–946] - Shi-Hao Wu; Xiao Li; Dong-Dong Qin; Lin-Heng Zhang; Tian-Lin Cheng; Zhi-Fang Chen; Bin-Bin Nie; Xiao-Feng Ren; Jing Wu; Wen-Chao Wang; Ying-Zhou Hu; Yi-lin Gu; et al. (Science Bulletin, 2023)

Gold − Titanium dioxide heterojunction for enhanced sonodynamic mediated biofilm eradication and peri-implant infection treatment - Fang Li; Qiyuan Pan; Yun Ling; Jingying Guo; Yaru Huo; Chao Xu; Manwen Xiong; Meng Yuan; Ziyong Cheng; Min Liu; Jun Lin (Chemical Engineering Journal, 2023)

Rapid shifts in thermal reaction norms and tolerance of brooded coral larvae following parental heat acclimation - Lei Jiang; Cheng‐Yue Liu; Guoxin Cui; Lin‐Tao Huang; Xiao‐Lei Yu; You‐Fang Sun; Hao‐Ya Tong; Guo‐Wei Zhou; Xiang‐Cheng Yuan; Yi‐Si Hu; Wen‐Liang Zhou; Manuel Aranda; et al. (Molecular Ecology, 2023)
Thermal priming of reef corals can enhance their heat tolerance; however, the legacy effects of heat stress during parental brooding on larval resilience remain understudied. This study investigated whether preconditioning adult coral Pocillopora damicornis to high temperatures (29°C and 32°C) could better prepare their larvae for heat stress. Results showed that heat‐acclimated adults brooded larvae with reduced symbiont density and shifted thermal performance curves. Reciprocal transplant experiments demonstrated higher bleaching resistance and better photosynthetic and autotrophic performance in heat‐exposed larvae from acclimated adults compared to unacclimated adults. RNA‐seq revealed strong cellular stress responses in larvae from heat‐acclimated adults that could have been effective in rescuing host cells from stress, as evidenced by the widespread upregulation of genes involved in cell cycle and mitosis. For symbionts, a molecular coordination between light harvesting, photoprotection and carbon fixation was detected in larvae from heat‐acclimated adults, which may help optimize photosynthetic activity and yield under high temperature. Furthermore, heat acclimation led to opposing regulations of symbiont catabolic and anabolic pathways and favoured nutrient translocation to the host and thus a functional symbiosis. Notwithstanding, the improved heat tolerance was paralleled by reduced light‐enhanced dark respiration, indicating metabolic depression for energy saving. Our findings suggest that adult heat acclimation can rapidly shift thermal tolerance of brooded coral larvae and provide integrated physiological and molecular evidence for this adaptive plasticity, which could increase climate resilience. However, the metabolic depression may be maladaptive for long‐term organismal performance, highlighting the importance of curbing carbon emissions to better protect corals.

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Modeling of an integrated H2S/NH3 scrubber and regeneration columns for coke oven gas purification - Hao-Jen Pan; Ming-Chun Fang; Jeffrey D. Ward; Hao-Yeh Lee; Hsun-Yu Lin; Cheng-Ting Hsieh; Chih-Lung Lee; Tzu-Hsien Huang; Yu-Chen Hsieh; Shih-Chieh Lin; Wei-Ti Chou (Journal of Cleaner Production, 2023)

Generating Sentinel-2 all-band 10-m data by sharpening 20/60-m bands: A hierarchical fusion network - Jingan Wu; Liupeng Lin; Chi Zhang; Tongwen Li; Xiao Cheng; Fang Nan (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2023)

Analyzing landslide-induced debris flow and flow-bridge interaction by using a hybrid model of depth-averaged model and discrete element method - Wen-Jie Shiu; Ching-Fang Lee; Chia-Chi Chiu; Meng-Chia Weng; Che-Ming Yang; Wei-An Chao; Chun-Yuan Liu; Cheng-Han Lin; Wei-Kai Huang (Landslides, 2023)

Combined effects of prenatal phthalate exposure on cardiometabolic risk score among 4- to 7-year-old children: MABC study - Hui Gao; Meng-long Geng; Juan Tong; Bao-lin Wang; Kun Huang; Yi Zhang; Hong Gan; Bei-bei Zhu; Peng Ding; Qu-nan Wang; Jian-qing Wang; Cheng Zhang; et al. (Chemosphere, 2023)

Two-stage dynamic data envelopment analysis measuring the overall efficiency and productivity changes of industry and agriculture in EU countries - Ching-Cheng Lu; I-Fang Lin; Tai-Yu Lin; Yung-ho Chiu (Journal of Cleaner Production, 2023)

Comparison of polycyclic aromatic hydrocarbon accumulation in crab tissues with the ambient marine particles from shallow hydrothermal vents, northeast Taiwan - Fang-Jing Deborah Lee; Jiang-Shiou Hwang; Jing-O Cheng; Huei-Ting Lin; Fung-Chi Ko (Environmental Research, 2023)

Selenium attenuates the association of co-exposure to arsenic, cadmium, and lead with cognitive function among Chinese community-dwelling older adults - Bei-Jing Cheng; Jie Sheng; Hong-Li Wang; Yuan Wang; Hong-Juan Cao; Xiu-De Li; Ting-Ting Zhou; Xiang-Long Meng; Huan-Huan Nie; Su-Fang Wang; Dong-Mei Zhang; Gui-Mei Chen; et al. (Environmental Science and Pollution Research, 2022)

The association between essential trace element mixture and atherosclerotic cardiovascular disease risk among Chinese community-dwelling older adults - Xiang-long Meng; Yuan Wang; Hong-li Wang; Huan-huan Nie; Bei-jing Cheng; Hong-juan Cao; Xiu-de Li; Su-fang Wang; Gui-mei Chen; Fang-biao Tao; Jie Sheng; Lin-sheng Yang (Environmental Science and Pollution Research, 2022)

A flocculation tensor to monitor water quality using a deep learning model - Guocheng Zhu; Jialin Lin; Haiquan Fang; Fang Yuan; Xiaoshang Li; Cheng Yuan; Andrew S. Hursthouse (Environmental Chemistry Letters, 2022)
The increasing quantities of polluted waters are calling for advanced purification methods. Flocculation is an essential component of the water purification process, yet flocculation is commonly not optimal due to our poor understanding of the flocculation process. In particular, there is little knowledge on the mechanisms ruling the migration of pollutants during treatment. Here we have created the first tensor diagram, a mathematical framework for the flocculation process, analyzed its properties with a deep learning model, and developed a classification scheme for its relationship with pollutants. The tensor was constructed by combining pixel matrices from a variety of floc images, each with a particular flocculation period. Changing the factors used to make flocs images, such as coagulant dose and pH, resulted in tensors, which were used to generate matrices, that is the tensor diagram. Our deep learning algorithm employed a tensor diagram to identify pollution levels. Results show tensor map attributes with over 98% of sample images correctly classified. This approach offers potential to reduce the time delay of feedback from the flocculation process with deep learning categorization based on its clustering capabilities. The advantage of the tensor data from the flocculation process improves the efficiency and speed of response for commercial water treatment.

An Analytical Solution of Transient Wave Generation in the Wave Channel - Cheng-Tsung Chen; Jaw-Fang Lee; Kuei-Ting Lin; Pi-Sheng Hu (Journal of Marine Science and Engineering, 2022)
Transient characteristics of wave generation in the wave channel can provide unique and important information in contrast to the steady and periodic motion of propagation waves. In this paper, a new analytical solution is proposed for a transient wavemaker problem in the wave channel. The mathematical model of the wavemaker problem is established based on the linear potential wave theory, and a new analytical solution for the corresponding initial and boundary-value problem is presented. The present solution methodology is motivated and developed from old methods shown in literature. The present solution can be mathematically reformulated and shown to be identical to the previous solution using different solution methodology. The present analytical solution is further compared with numerical results and experiments to validate the mathematical model. The present solution is used to calculate the steady state generated wave forms that compare very well with the steady wave theory both in wave length and wave period. The present solution is also used to study unsteady characteristics of wave heights and wave lengths of the leading waves. The present analytical solution methodology can provide an easier approach to obtain the analytical solution for transient wave generation problem in the wave channel.

Isolation and identification of two new sargentodoxosides from Sargentodoxa cuneata and their agonistic effects against FXR - Wen Zhang; Cheng-Peng Sun; Yu-Lin Peng; Wen-Yu Zhao; Zheng-Yue Wang; Jing Ning; Xia Lv; Zhen-Long Yu; Shuang Zhou; Wei Peng; Bang-Jiang Fang; Xiao-Chi Ma (Natural Product Research, 2022)

A Time-Domain Analytic Solution of Flow-Induced Undular Bores - Cheng-Tsung Chen; Jaw-Fang Lee; Hubert Chanson; Kuei-Ting Lin; Chun-Jih Lin (Journal of Marine Science and Engineering, 2022)
In this study, the problem of surface waves induced by water flow in a flow channel was investigated. The mathematical model based on the potential wave theory was established, and a new analytic solution to the corresponding initial and boundary value problem was proposed. To confirm our analytic solution, the mathematical model was applied to simulate experiments conducted in a flow channel in the laboratory. Using our analytic solution, water surface elevations and flow velocities at certain locations in the channel were compared with experimental results. Comparisons between our analytic solution and experimental results confirmed our theory that amplitudes and propagating phases are in very close agreement. Our analytic solution can be used to calculate variations in pressure and velocity along the water depth, which are expensive to calibrate and obtain in experiments. Although our analytic solution was established based on linear theory, it is very practical for applications studying the basic properties of surface elevation, velocity, and pressure of the flow field induced by water current both in space and time.

Bioeconomic evaluation of Eleutheronema tetradactylum farming: a case study in Taiwan - Cheng-Ting Huang; Farok Afero; Fang-Yu Lu; Bo-Ying Chen; Po-Lin Huang; Hsun-Yu Lan; Yen-Lung Hou (Fisheries Science, 2022)

Isolation and identification of new source of bacteriocin-producing Lactobacillus plantarum C010 and growth kinetics of its batch fermentation - Jinyue Dai; Limin Fang; Manmin Zhang; Huaili Deng; Xin Cheng; Mingyin Yao; Lin Huang (World Journal of Microbiology and Biotechnology, 2022)

Towards a rapid assessment of highway slope disasters by using multidisciplinary techniques - Meng-Chia Weng; Cheng-Han Lin; Wen-Jie Shiu; Wei-An Chao; Chia-Chi Chiu; Ching-Fang Lee; Wei-Kai Huang; Che-Ming Yang (Landslides, 2022)
Mega-earthquakes and extreme climate events accompanied by intrinsic fragile geology lead to numerous landslides along mountain highways in Taiwan, causing enormous life and economic losses. In this study, a system for rapid slope disaster information integration and assessment is proposed with the aim of providing information on landslide occurrence, failure mechanisms, and subsequent landslide-affected areas to the highway authority rapidly. The functionality of the proposed system is deployed into three units: (1) geohazard rapid report (GeoPORT I), (2) multidisciplinary geological survey report (GeoPORT II), and (3) site-specific landslide simulation report (GeoPORT III). After landslide occurrence, the seismology-based monitoring network rapidly provides the initial slope disaster information, including preliminary location, event magnitude, earthquake activity, and source dynamics, within an hour. Within 3 days of the landslide, a multidisciplinary geological survey is conducted to collect high-precision topographical, geological, and remote-sensing data to determine the possible failure mechanism. After integrating the aforementioned information, a full-scale three-dimensional landslide simulation based on the discrete element method is performed within 10 days to reveal the failure process and to identify the areas potentially affected by subsequent disasters through scenario modeling. Overall, the proposed system can promptly provide comprehensive and objective information to relevant authorities after the event occurrence for hazard assessment. The proposed system was validated using a landslide event in the Central Cross-Island Highway of Taiwan.

Demersal fish diversity and molecular taxonomy in the Bering Sea and Chukchi Sea - Hai Li; Fang Yang; Xuehua Wang; Yuan Li; Nan Zhang; Ran Zhang; Cheng Liu; Hushun Zhang; Longshan Lin; Puqing Song (Conservation Genetics Resources, 2022)

L-Theanine Ameliorated Rotenone-Induced Parkinsonism-like Symptoms in Rats - Cheng-Neng Chen; Mao-Hsien Wang; Hung-Sheng Soung; Shu-Mei Chen; Chih-Hsiang Fang; Yi-Wen Lin; Hsiang-Chien Tseng (Neurotoxicity Research, 2022)

Marinomonas vulgaris sp. nov., a marine bacterium isolated from seawater in a coastal intertidal zone of Zhoushan island - Jun-Jie Ying; Yuan-Chun Fang; Yong-Lian Ye; Zhi-Cheng Wu; Lin Xu; Bing-Nan Han; Cong Sun (Archives of Microbiology, 2021)

RSF1 requires CEBP/β and hSNF2H to promote IL-1β-mediated angiogenesis: the clinical and therapeutic relevance of RSF1 overexpression and amplification in myxofibrosarcomas - Chien-Feng Li; Ti-Chen Chan; Cheng-I. Wang; Fu-Min Fang; Po-Chun Lin; Shih-Chen Yu; Hsuan-Ying Huang (Angiogenesis, 2021)

Dynamic Anthropometrics of Preschool Children in Taiwan for Playground Equipment Designs - I-Fang Cheng; Chien-Ju Lin; Li-Chieh Kuo; Bih-Jen Hsue; Fong-Chin Su (Journal of Medical and Biological Engineering, 2021)

Crenobacter intestini sp. nov., Isolated from the Intestinal Tract of Konosirus punctatus - Song-Biao Shi; Jia-Fa Wu; Li-Fang Yang; Ming-Guo Jiang; Cai-Mi Gao; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2021)

Effects of degradation succession of alpine wetland on soil organic carbon and total nitrogen in the Yellow River source zone, west China - Chun-ying Lin; Xi-lai Li; Jing Zhang; Hua-fang Sun; Juan Zhang; Hui-bang Han; Qi-hua Wang; Cheng-biao Ma; Cheng-yi Li; Yu-xing Zhang; Xue-qian Ma (Journal of Mountain Science, 2021)

Co-transport of biochar colloids with organic contaminants in soil column - Rashida Hameed; Cheng Lei; Jing Fang; Daohui Lin (Environmental Science and Pollution Research, 2021)

A calculation model to assess the crack propagation length of rock block in clastic flow - Yang Liu; Yong You; Jin-feng Liu; Shu-xi Zhao; Dong-xu Yang; Dao-chuan Liu; Lin Liu; Yan-fang Xie; Kai-cheng Yang (Journal of Mountain Science, 2020)

Matriptase and prostasin proteolytic activities are differentially regulated in normal and wounded skin - Shun-Cheng Chang; Chien-Ping Chiang; Chih-Hsin Lai; Po-Wen A. Du; Yu-Sin Hung; Yu-Hsuan Chen; Hui-Yu Yang; Hao-Yu Fang; Shiao-Pieng Lee; Hung-Jen Tang; Jehng-Kang Wang; Michael D. Johnson; et al. (Human Cell, 2020)

Reversal of Social Recognition Deficit in Adult Mice with MECP2 Duplication via Normalization of MeCP2 in the Medial Prefrontal Cortex - Bin Yu; Bo Yuan; Jian-Kun Dai; Tian-lin Cheng; Sheng-Nan Xia; Ling-Jie He; Yi-Ting Yuan; Yue-Fang Zhang; Hua-Tai Xu; Fu-Qiang Xu; Zhi-Feng Liang; Zi-Long Qiu (Neuroscience Bulletin, 2020)

Nanochemoprevention with therapeutic benefits: An updated review focused on epigallocatechin gallate delivery - Qiong-Qiong Yang; Xin-Lin Wei; Ya-Peng Fang; Ren-You Gan; Min Wang; Ying-Ying Ge; Dan Zhang; Li-Zeng Cheng; Harold Corke (Critical Reviews in Food Science and Nutrition, 2020)

Impacts of elevated temperature and pCO2 on the brooded larvae of Pocillopora damicornis from Luhuitou Reef, China: evidence for local acclimatization - Lei Jiang; Ming-Lan Guo; Fang Zhang; Yu-Yang Zhang; Guo-Wei Zhou; Xin-Ming Lei; Xiang-Cheng Yuan; You-Fang Sun; Tao Yuan; Lin Cai; Jian-Sheng Lian; Sheng Liu; et al. (Coral Reefs, 2020)

Protective Effect of (−)Epigallocatechin-3-gallate on Rotenone-Induced Parkinsonism-like Symptoms in Rats - Hsiang-Chien Tseng; Mao-Hsien Wang; Kuo-Chi Chang; Hung-Sheng Soung; Chih-Hsiang Fang; Yi-Wen Lin; Keng-Yuan Li; Chih-Chuan Yang; Cheng-Chia Tsai (Neurotoxicity Research, 2020)

MicroRNA-mediated responses to colchicine treatment in barley - Fang-Yao Sun; Lin Liu; Yi Yu; Xin-Ming Ruan; Cheng-Yu Wang; Qun-Wen Hu; De-Xiang Wu; Genlou Sun (Planta, 2020)

Therapeutic Efficacy of Subcutaneous and Intraperitoneal Injections of a Single Dose of Human Umbilical Mesenchymal Stem Cells in Acute and Chronic Colitis in a Mouse Model - Yu-Lung Chang; Huei-Yu Lo; Shun-Ping Cheng; Kuo-Ting Chang; Xiu-Fang Lin; Sheng-Ping Lee; Jason Ma; Ming-Ling Kuo; Ming-Fa Hsieh; Chin-Kan Chan (Journal of Medical and Biological Engineering, 2020)

Implementation of the Land Surface Processes into a Vector Vorticity Equation Model (VVM) to Study its Impact on Afternoon Thunderstorms over Complex Topography in Taiwan - Chien-Ming Wu; Hsiao-Chun Lin; Fang-Yi Cheng; Mu-Hua Chien (Asia-Pacific Journal of Atmospheric Sciences, 2019)

Ottowia flava sp. nov., isolated from fish intestines - Song-Biao Shi; Gui-Ding Li; Li-Fang Yang; Cong Liu; Ming-Guo Jiang; Qin-Yuan Li; Jia-Fa Wu; Kun Zhang; Long-Qian Jiang; Nai-Kun Shen; Cheng-Lin Jiang; Yi Jiang (Antonie van Leeuwenhoek, 2019)

Rab18 Collaborates with Rab7 to Modulate Lysosomal and Autophagy Activities in the Nervous System: an Overlapping Mechanism for Warburg Micro Syndrome and Charcot-Marie-Tooth Neuropathy Type 2B - Fang-Shin Nian; Lei-Li Li; Chih-Ya Cheng; Pei-Chun Wu; You-Tai Lin; Cheng-Yung Tang; Bo-Shiun Ren; Chin-Yin Tai; Ming-Ji Fann; Lung-Sen Kao; Chen-Jee Hong; Jin-Wu Tsai (Molecular Neurobiology, 2019)

Anthropometric Database of the Preschool Children from 2 to 6 Years in Taiwan - I-Fang Cheng; Li-Chieh Kuo; Chien-Ju Lin; Hsiao-Feng Chieh; Fong-Chin Su (Journal of Medical and Biological Engineering, 2019)

Distribution of mercury and methylmercury in surface water and surface sediment of river, irrigation canal, reservoir, and wetland in Taiwan - Ying-Lin Wang; Meng-Der Fang; Ling-Chu Chien; Chu-Ching Lin; Hsing-Cheng Hsi (Environmental Science and Pollution Research, 2019)

Neonatal Dexamethasone Treatment Suppresses Hippocampal Estrogen Receptor α Expression in Adolescent Female Rats - Hui-Fang Chiu; Michael W. Y. Chan; Chiung-Yin Cheng; Jian-Liang Chou; Jora Meng-Ju Lin; Yi-Ling Yang; Kwok-Tung Lu (Molecular Neurobiology, 2019)

Genome-wide analysis identified 17 new loci influencing intraocular pressure in Chinese population - Lulin Huang; Yuhong Chen; Ying Lin; Pancy O. S. Tam; Yilian Cheng; Yi Shi; Bo Gong; Fang Lu; Jialiang Yang; Haixin Wang; Yi Yin; Yong Cao; et al. (Science China Life Sciences, 2019)

Adenosine Augmentation Evoked by an ENT1 Inhibitor Improves Memory Impairment and Neuronal Plasticity in the APP/PS1 Mouse Model of Alzheimer’s Disease - Chia-Chia Lee; Ching-Pang Chang; Chun-Jung Lin; Hsing-Lin Lai; Yu-Han Kao; Sin-Jhong Cheng; Hui-Mei Chen; Yu-Ping Liao; Emilie Faivre; Luc Buée; David Blum; Jim-Min Fang; et al. (Molecular Neurobiology, 2018)

Immune Cells After Ischemic Stroke Onset: Roles, Migration, and Target Intervention - Lu-yao Ao; Yun-Yi Yan; Lin Zhou; Cheng-yuan Li; Wan-Ting Li; Wei-rong Fang; Yun-man Li (Journal of Molecular Neuroscience, 2018)

Toward a higher yield: a wireless sensor network-based temperature monitoring and fan-circulating system for precision cultivation in plant factories - Joe-Air Jiang; Min-Sheng Liao; Tzu-Shiang Lin; Chen-Kang Huang; Cheng-Ying Chou; Shih-Hao Yeh; Ta-Te Lin; Wei Fang (Precision Agriculture, 2018)

Regulatory Effects of Neuroinflammatory Responses Through Brain-Derived Neurotrophic Factor Signaling in Microglial Cells - Sheng-Wei Lai; Jia-Hong Chen; Hsiao-Yun Lin; Yu-Shu Liu; Cheng-Fang Tsai; Pei-Chun Chang; Dah-Yuu Lu; Chingju Lin (Molecular Neurobiology, 2018)

Identification of a new type tadalafil analogue in a supplement product - Yen-Chun Huang; Hui-Chun Lee; Yun-Lian Lin; Chia-Fen Tsai; Hwei-Fang Cheng (Food Additives & Contaminants: Part A, 2018)

Effect of pad-fan cooling and dietary organic acid supplementation during late gestation and lactation on reproductive performance and antioxidant status of multiparous sows in hot weather - Jun Chen; Ji Guo; Wu-tai Guan; Jun-Jie Song; Zi-Xiao Deng; Lin Cheng; Yue-Lin Deng; Fang Chen; Shi-Hai Zhang; Yin-Zi Zhang; Fei Yang; Chun-Xiao Ren; et al. (Tropical Animal Health and Production, 2018)

Identifying potentially common genes between dyslipidemia and osteoporosis using novel analytical approaches - Xu Lin; Cheng Peng; Jonathan Greenbaum; Zhang-Fang Li; Ke-Hao Wu; Zeng-Xin Ao; Tong Zhang; Jie Shen; Hong-Wen Deng (Molecular Genetics and Genomics, 2018)

The Distal Gut Bacterial Community of Some Primates and Carnivora - Xiu Chen; Qin-Yuan Li; Gui-Ding Li; Fang-Ji Xu; Li Han; Yi Jiang; Xue-Shi Huang; Cheng-Lin Jiang (Current Microbiology, 2018)

Efficient Using Durian Shell Hydrolysate as Low-Cost Substrate for Bacterial Cellulose Production by Gluconacetobacter xylinus - Mu-Tan Luo; Cheng Zhao; Chao Huang; Xue-Fang Chen; Qian-Lin Huang; Gao-Xiang Qi; Lan-Lan Tian; Lian Xiong; Hai-Long Li; Xin-De Chen (Indian Journal of Microbiology, 2017)

Effect of culture conditions on metabolites produced by the crinoid-derived fungus Aspergillus ruber 1017 - Yong-Fang Li; Xue-Bin Wu; Shah-Iram Niaz; Liu-Hong Zhang; Zhi-Jian Huang; Yong-Cheng Lin; Jing Li; Lan Liu (Natural Product Research, 2017)

Morphology and controlling factors of the longitudinal profile of gullies in the Yuanmou dry-hot valley - Lin Ding; Fa-chao Qin; Hai-dong Fang; Hui Liu; Bin Zhang; Cheng-qiang Shu; Qing-chun Deng; Gang-cai Liu; Qian-qian Yang (Journal of Mountain Science, 2017)

Isolation and identification of a novel sildenafil analogue adulterant in herbal products - Ya-Tze Lin; Yen-Chun Huang; Hui-Chun Lee; Chen-Hsiang Liao; Yun-Lian Lin; Chia-Fen Tsai; Hwei-Fang Cheng (Food Additives & Contaminants: Part A, 2017)

Development of a fluorescence resonance energy transfer–based intracellular assay to identify novel enterovirus 71 antivirals - Wen-Wen Lu; Fang-Yen Kung; Po-An Deng; Yu-Chu Lin; Cheng-Wen Lin; Szu-Hao Kung (Archives of Virology, 2017)

Impacts of sediment type on the performance and composition of submerged macrophyte communities - Lin Liu; Xiang-Qi Bu; Jun-Yan Wan; Bi-Cheng Dong; Fang-Li Luo; Hong-Li Li; Fei-Hai Yu (Aquatic Ecology, 2017)

Novel interaction between CCR4 and CAF1 in rice CCR4–NOT deadenylase complex - Wei-Lun Chou; Yue-Lin Chung; Jhen-Cheng Fang; Chung-An Lu (Plant Molecular Biology, 2017)

Identification of a new sildenafil analogue adulterant, desethylcarbodenafil, in a herbal supplement - Yen-Chun Huang; Hui-Chun Lee; Yun-Lian Lin; Ya-Tze Lin; Chia-Fen Tsai; Hwei-Fang Cheng (Food Additives & Contaminants: Part A, 2016)

Interlukin-18 Is a Pivot Regulatory Factor on Matrix Metalloproteinase-13 Expression and Brain Astrocytic Migration - Jia-Hong Chen; Chon-Haw Tsai; Hsiao-Yun Lin; Chien-Fang Huang; Yuk-Man Leung; Sheng-Wei Lai; Cheng-Fang Tsai; Pei-Chun Chang; Dah-Yuu Lu; Chingju Lin (Molecular Neurobiology, 2016)

Characteristics of soil CO2 efflux under an invasive species, Moso bamboo, in forests of central Taiwan - I-Fang Hsieh; Tomonori Kume; Meng-Ying Lin; Chih-Hsin Cheng; Takeshi Miki (Trees, 2016)

Associations of TNF-α and IL-6 polymorphisms with osteoporosis through joint effects and interactions with LEPR gene in Taiwan: Taichung Community Health Study for Elders (TCHS-E) - Cheng-Chieh Lin; Tsai-Chung Li; Chiu-Shong Liu; Chuan-Wei Yang; Chih-Hsueh Lin; Jen-Hao Hsiao; Nai-Hsin Meng; Wen-Yuan Lin; Li-Na Liao; Chia-Ing Li; Fang-Yang Wu (Molecular Biology Reports, 2016)

The P450 oxidoreductase (POR) rs2868177 and cytochrome P450 (CYP) 2B6*6 polymorphisms contribute to the interindividual variability in human CYP2B6 activity - Li-chen Gao; Fang-qun Liu; Li Yang; Lin Cheng; Hai-ying Dai; Ran Tao; Shi-Peng Cao; Di Wang; Jie Tang (European Journal of Clinical Pharmacology, 2016)

Cobalt Protoporphyrin Upregulates Cyclooxygenase-2 Expression Through a Heme Oxygenase-Independent Mechanism - Hsiao-Yun Lin; Chon-Haw Tsai; Chingju Lin; Wei-Lan Yeh; Cheng-Fang Tsai; Pei-Chun Chang; Ling-Hsuan Wu; Dah-Yuu Lu (Molecular Neurobiology, 2016)

Allergy symptoms, serum total immunoglobulin E, and risk of head and neck cancer - Hsiao-Chen Liao; Shang-Yin Wu; Chun-Yen Ou; Jenn-Ren Hsiao; Jehn-Shyun Huang; Sen-Tien Tsai; Cheng-Chih Huang; Tung-Yiu Wong; Wei-Ting Lee; Ken-Chung Chen; Sheen-Yie Fang; Jiunn-Liang Wu; et al. (Cancer Causes & Control, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Microbacterium gilvum sp. nov., isolated from civet faeces - Xiu Chen; Qin-Yuan Li; Gui-Ding Li; Fang-Ji Xu; Yi Jiang; Li Han; Cheng-Lin Jiang; Xue-Shi Huang (Antonie van Leeuwenhoek, 2016)

Atmospheric polycyclic aromatic hydrocarbons (PAHs) of southern Taiwan in relation to monsoons - Jing-O Cheng; Fung-Chi Ko; Chon-Lin Lee; Meng-Der Fang (Environmental Science and Pollution Research, 2016)

Leifiporia rhizomorpha gen. et sp. nov. and L. eucalypti comb. nov. in Polyporaceae (Basidiomycota) - Chang-Lin Zhao; Fang Wu; Yu-Cheng Dai (Mycological Progress, 2016)

Identification of a new tadalafil analogue, dipropylaminopretadalafil, in a dietary supplement - Yen-Chun Huang; Hui-Chun Lee; Yun-Lian Lin; Chia-Fen Tsai; Hwei-Fang Cheng (Food Additives & Contaminants: Part A, 2016)

Complete genome sequence of the cold-active bacteriophage VMY22 from Bacillus cereus - Kunhao Qin; Benxu Cheng; Shengting Zhang; Nan Wang; Yuan Fang; Qi Zhang; Anxiu Kuang; Lianbing Lin; Xiuling Ji; Yunlin Wei (Virus Genes, 2016)

Naringenin Suppresses Neuroinflammatory Responses Through Inducing Suppressor of Cytokine Signaling 3 Expression - Ling-Hsuan Wu; Chingju Lin; Hsiao-Yun Lin; Yu-Shu Liu; Caren Yu-Ju Wu; Cheng-Fang Tsai; Pei-Chun Chang; Wei-Lan Yeh; Dah-Yuu Lu (Molecular Neurobiology, 2016)

Six new metabolites produced by Colletotrichum aotearoa 09F0161, an endophytic fungus isolated from Bredia oldhamii - Yi Hsiao; Ming-Jen Cheng; Hsun-Shuo Chang; Ming-Der Wu; Sung-Yuan Hsieh; Ta-Wei Liu; Chu-Hung Lin; Gwo-Fang Yuan; Ih-Sheng Chen (Natural Product Research, 2016)

Ambient air particulates and particulate-bound mercury Hg(p) concentrations: dry deposition study over a Traffic, Airport, Park (T.A.P.) areas during years of 2011–2012 - Guor-Cheng Fang; Yen-Heng Lin; Yu-Cheng Zheng (Environmental Geochemistry and Health, 2016)

Jasmonic acid involves in grape fruit ripening and resistant against Botrytis cinerea - Haifeng Jia; Cheng Zhang; Tariq Pervaiz; Pengcheng Zhao; Zhongjie Liu; Baoju Wang; Chen Wang; Lin Zhang; Jinggui Fang; Jianpu Qian (Functional & Integrative Genomics, 2016)

Development of single-chain variable fragments (scFv) against influenza virus targeting hemagglutinin subunit 2 (HA2) - Tai-Wei Li; Shu-Fang Cheng; Yen-Tzu Tseng; Yu-Chih Yang; Wen-chun Liu; Sheng-Cyuan Wang; Mei-Ju Chou; Yu-Jen Lin; Yueh Wang; Pei-Wen Hsiao; Suh-Chin Wu; Ding-Kwo Chang (Archives of Virology, 2016)

Separation and identification of a novel tadalafil analogue adulterant in a dietary supplement - Yen-Chun Huang; Hui-Chun Lee; Yun-Lian Lin; Chia-Ying Li; Chia-Fen Tsai; Hwei-Fang Cheng (Food Additives & Contaminants: Part A, 2015)

G206D Mutation of Presenilin-1 Reduces Pen2 Interaction, Increases Aβ42/Aβ40 Ratio and Elevates ER Ca2+ Accumulation - Wei-Ting Chen; Yi-Fang Hsieh; Yan-Jing Huang; Che-Ching Lin; Yen-Tung Lin; Yu-Chao Liu; Cheng-Chang Lien; Irene Han-Juo Cheng (Molecular Neurobiology, 2015)

Sphingobacterium rhinocerotis sp. nov., isolated from the faeces of Rhinoceros unicornis - Gui-Ding Li; Xiu Chen; Qin-Yuan Li; Fang-Ji Xu; Shu-Mei Qiu; Yi Jiang; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2015)

Mitoflash altered by metabolic stress in insulin-resistant skeletal muscle - Yi Ding; Huaqiang Fang; Wei Shang; Yao Xiao; Tao Sun; Ning Hou; Lin Pan; Xueting Sun; Qi Ma; Jingsong Zhou; Xianhua Wang; Xiuqin Zhang; et al. (Journal of Molecular Medicine, 2015)

Conjugated linoleic acid alters growth performance, tissue lipid deposition, and fatty acid composition of darkbarbel catfish (Pelteobagrus vachelli) - Gui-Fang Dong; Wen-Zuo Liu; Lin-Zhou Wu; Deng-hang Yu; Feng Huang; Peng-Cheng Li; Yan-ou Yang (Fish Physiology and Biochemistry, 2015)

Enrichment of cardiac differentiation by a large starting number of embryonic stem cells in embryoid bodies is mediated by the Wnt11-JNK pathway - Ming Chen; Cheng Qian; Lin-Lin Bi; Fang Zhao; Guang-Yu Zhang; Zhi-Quan Wang; Xue-Dong Gan; Yang-Gan Wang (Biotechnology Letters, 2015)

Genetic association study between INSULIN pathway related genes and high myopia in a Han Chinese population - Xiaoqi Liu; Pu Wang; Chao Qu; Hong Zheng; Bo Gong; Shi Ma; He Lin; Jing Cheng; Zhenglin Yang; Fang Lu; Yi Shi (Molecular Biology Reports, 2015)

Concentrations of particulates in ambient air, gaseous elementary mercury (GEM), and particulate-bound mercury (Hg(p)) at a traffic sampling site: a study of dry deposition in daytime and nighttime - Guor-Cheng Fang; Yen-Heng Lin; Chia-Ying Chang; Yu-Cheng Zheng (Environmental Geochemistry and Health, 2014)

Cingulum Correlates of Cognitive Functions in Patients with Mild Cognitive Impairment and Early Alzheimer’s Disease: A Diffusion Spectrum Imaging Study - Yi-Cheng Lin; Yao-Chia Shih; Wen-Yih I. Tseng; Yu-Hsiu Chu; Meng-Tien Wu; Ta-Fu Chen; Pei-Fang Tang; Ming-Jang Chiu (Brain Topography, 2014)

Unpalatable weed Stellera chamaejasme L. provides biotic refuge for neighboring species and conserves plant diversity in overgrazing alpine meadows on the Tibetan Plateau in China - Wei Cheng; Geng Sun; Lin-fang Du; Yan Wu; Qun-ying Zheng; Hong-xuan Zhang; Lin Liu; Ning Wu (Journal of Mountain Science, 2014)

Genetic variation in alkaloid accumulation in leaves of Nicotiana - Bo Sun; Fen Zhang; Guo-jun Zhou; Guo-hai Chu; Fang-fang Huang; Qiao-mei Wang; Li-feng Jin; Fu-cheng Lin; Jun Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Prognostic value of HIF-1α expression in patients with gastric cancer - Cheng-lin Zhu; Qiang Huang; Chen-hai Liu; Xian-sheng Lin; Fang Xie (Molecular Biology Reports, 2013)

Hesperetin protects against cardiac remodelling induced by pressure overload in mice - Wei Deng; Duan Jiang; Yi Fang; Heng Zhou; Zhihong Cheng; Yafen Lin; Rui Zhang; Jieyu Zhang; Peng Pu; Yuan Liu; Zhouyan Bian; Qizhu Tang (Journal of Molecular Histology, 2013)

Analysis of artificial corner reflector’s radar cross section: a physical optics perspective - Xin-Jian Shan; Jing-Yuan Yin; Dan-Lin Yu; Cheng-Fan Li; Jun-Juan Zhao; Gui-Fang Zhang (Arabian Journal of Geosciences, 2013)

Monascusazaphilones A–C, three new azaphilone analogues isolated from the fungus Monascus purpureus BCRC 38108 - Ming-Der Wu; Ming-Jen Cheng; Yi-Jen Yech; Yen-Lin Chen; Kai-Ping Chen; Ping-Hsun Yang; Ih-Sheng Chen; Gwo-Fang Yuan (Natural Product Research, 2013)

Estimation of phosphorus flux in rivers during flooding - Yen-Chang Chen; Jih-Hung Liu; Jan-Tai Kuo; Cheng-Fang Lin (Environmental Monitoring and Assessment, 2013)

Proteomic and physiological analyses reveal detoxification and antioxidation induced by Cd stress in Kandelia candel roots - Zhao-Xia Weng; Ling-Xia Wang; Fang-lin Tan; Li Huang; Jian-Hong Xing; Shi-Pin Chen; Chi-Lien Cheng; Wei Chen (Trees, 2013)

Trace Element, Antioxidant Activity, and Lipid Peroxidation Levels in Brain Cortex of Gerbils After Cerebral Ischemic Injury - Kwang-Ming Fang; Fu-Chou Cheng; Yeou-Lih Huang; Shu-Ying Chung; Zhong-Yang Jian; Ming-Cheng Lin (Biological Trace Element Research, 2013)

Recombined sequences between the non-coding control regions of JC and BK viruses found in the urine of a renal transplantation patient - Yu-Ching Liaw; Cheng-Hsu Chen; Kuo-Hsiung Shu; Chiung-Yao Fang; Wei-Chih Ou; Pei-Lain Chen; Cheng-Huang Shen; Mien-Chun Lin; Deching Chang; Meilin Wang (Virus Genes, 2012)

Polymorphisms in the cytotoxic T-lymphocyte antigen 4 gene and acute rejection risk in transplant recipients - Cheng-lin Zhu; Qiang Huang; Chen-hai Liu; Fang Xie (Molecular Biology Reports, 2012)

Co-occurrence of arseniasis and fluorosis due to indoor combustion of high fluorine and arsenic content coal in a rural township in northwest China: epidemiological and toxicological aspects - Guo-fang Lin; Shi-you Gong; Cheng Wei; Ji-gang Chen; Klaus Golka; Jian-hua Shen (Archives of Toxicology, 2012)

Interaction between iron plaque and root border cells ameliorates aluminum toxicity of Oryza sativa differing in aluminum tolerance - Miao-Zhen Cai; Shu-Na Zhang; Cheng-Hua Xing; Fang-Mei Wang; Lei Zhu; Ning Wang; Li-Yu Lin (Plant and Soil, 2012)

An upstream regulatory element confers orientation-independent enhancement of the TSG101 promoter activity in transformed cells - Shih-Fang Hsu; Yih-Gang Goan; Hsien-Yu Tsai; Yi-Ru Lin; Rue-Tsuan Liu; Jiin-Tsuey Cheng (Molecular Biology Reports, 2012)

The relationship between competitive ability and yield stability in an old and a modern winter wheat cultivar - Yan Fang; Lin Liu; Bing-Cheng Xu; Feng-Min Li (Plant and Soil, 2011)

Trichodermanin A, a novel diterpenoid from endophytic fungus culture - Pei-Xin Sun; Cheng-Jian Zheng; Wen-Chao Li; Gui-Lin Jin; Fang Huang; Lu-Ping Qin (Journal of Natural Medicines, 2011)

Prevention of cerebral ischemia-induced memory deficits by inhibition of phosphodiesterase-4 in rats - Ling-Xia Li; Yu-Fang Cheng; Huan-Bing Lin; Chuang Wang; Jiang-Ping Xu; Han-Ting Zhang (Metabolic Brain Disease, 2011)

Bacillus deserti sp. nov., a novel bacterium isolated from the desert of Xinjiang, China - Lei Zhang; Gao-Lin Wu; Yang Wang; Jun Dai; Cheng-Xiang Fang (Antonie van Leeuwenhoek, 2011)

Point patterns of tree distribution determined by habitat heterogeneity and dispersal limitation - Yi-Ching Lin; Li-Wan Chang; Kuoh-Cheng Yang; Hsiang-Hua Wang; I-Fang Sun (Oecologia, 2011)

Dietary patterns and breast cancer risk among Chinese women - Cai-Xia Zhang; Suzanne C. Ho; Jian-Hua Fu; Shou-Zhen Cheng; Yu-Ming Chen; Fang-Yu Lin (Cancer Causes & Control, 2011)

Honokiol: an effective inhibitor of high-glucose-induced upregulation of inflammatory cytokine production in human renal mesangial cells - Jian-Ping Wu; Wei Zhang; Fang Wu; Ying Zhao; Lin-Fang Cheng; Jun-Jun Xie; Hang-Ping Yao (Inflammation Research, 2010)

Molecular phylogeny of Ranunculaceae based on rbc L sequences - Ying-fan Cai; Sheng-wei Li; Min Chen; Ming-feng Jiang; Yi Liu; Yong-fang Xie; Quan Sun; Huai-zhong Jiang; Neng-wen Yin; Ling Wang; Rui Zhang; Cheng-lin Huang; et al. (Biologia, 2010)

Inhibition of phosphodiesterase-4 reverses memory deficits produced by Aβ25–35 or Aβ1–40 peptide in rats - Yu-Fang Cheng; Chuang Wang; Huan-Bing Lin; Yun-Feng Li; Ying Huang; Jiang-Ping Xu; Han-Ting Zhang (Psychopharmacology, 2010)

Angiotensin-converting enzyme 2 (ACE2) proteins of different bat species confer variable susceptibility to SARS-CoV entry - Yuxuan Hou; Cheng Peng; Meng Yu; Yan Li; Zhenggang Han; Fang Li; Lin-Fa Wang; Zhengli Shi (Archives of Virology, 2010)

Characterization of the Scutellaria barbata glycosyltransferase gene and its promoter - Shu-Jiau Chiou; Wen-Yu Liu; Cheng-Li Fang; Tsai-Yun Lin (Planta, 2010)

Season variations for metallic elements compositions study in plant Bidenens pilosa L. var. radiate Sch. in central Taiwan - Yuh-Shen Wu; Guor-Cheng Fang; Shun-Hisu Lin (Environmental Monitoring and Assessment, 2010)

A Preliminary Assessment of Polycyclic Aromatic Hydrocarbon Distribution in the Kenting Coral Reef Waters of Southern Taiwan - Jing-O. Cheng; Ying-Ming Cheng; Te-Hao Chen; Ping-Chieh Hsieh; Meng-Der Fang; Chon-Lin Lee; Fung-Chi Ko (Archives of Environmental Contamination and Toxicology, 2010)

Construction of a recombinant adenovirus vector expressing IL-18BP/IL-4 fusion gene and the anti-inflammatory effect induced by this gene on lipopolysaccharide-stimulated synovial fibroblasts - Hang-Ping Yao; Yun Qian; Xue-Ting Shao; Zhe-Rong Xu; Lin-Fang Cheng; Lei Feng; Nan-Ping Wu; Yun-Mei Yang (Inflammation Research, 2010)

Cloning and Characterization of ApRab4, a Recycling Rab Protein of Aiptasia pulchella, and Its Implication in the Symbiosome Biogenesis - Ming-Cheng Hong; Yung-Sen Huang; Pa-Ching Song; Wen-Wen Lin; Lee-Shing Fang; Ming-Chyuan Chen (Marine Biotechnology, 2009)

Meat and egg consumption and risk of breast cancer among Chinese women - Cai-Xia Zhang; Suzanne C. Ho; Yu-Ming Chen; Fang-Yu Lin; Jian-Hua Fu; Shou-Zhen Cheng (Cancer Causes & Control, 2009)

Memory deficits and neurochemical changes induced by C-reactive protein in rats: implication in Alzheimer’s disease - Huan-Bing Lin; Xue-Mei Yang; Tie-Jun Li; Yu-Fang Cheng; Han-Ting Zhang; Jiang-Ping Xu (Psychopharmacology, 2009)

Early transcriptional deregulation of hepatic mitochondrial biogenesis and its consequent effects on murine cholestatic liver injury - Mao-Meng Tiao; Tsu-Kung Lin; Cha-Wei Liou; Pei-Wen Wang; Jin-Bor Chen; Fang-Ying Kuo; Chao-Cheng Huang; Yao-Min Chou; Jiin-Haur Chuang (Apoptosis, 2009)

Recombinant ORF66 and ORFK12 antigens for the detection of human herpesvirus 8 antibodies in HIV-positive and -negative patients - Tsuey-Ching Yang; Chun-Pin Chang; Yu-Ching Lan; Chao-Li Liu; Mu-Chin Shih; Fang-Yang Wu; Cheng-Wen Lin (Biotechnology Letters, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Effect of calmidazolium on [Ca2+]i and viability in human hepatoma cells - Wei-Chuan Liao; Chorng-Chih Huang; He-Hsiung Cheng; Jue-Long Wang; Ko-Long Lin; Jin-Shiung Cheng; Kuo-Liang Chai; Pei-Te Hsu; Jeng-Yu Tsai; Yi-Chien Fang; Yih-Chau Lu; Hong-Tai Chang; et al. (Archives of Toxicology, 2009)

Dry deposition study by using dry deposition plate and water surface sampler in Shalu, central Taiwan - Chia-Chun Chu; Guor-Cheng Fang; Jhy-Cherng Chen; I-Lin Yang (Environmental Monitoring and Assessment, 2008)

White-spot disease of Chinese soft-shelled turtles (Trionyx sinens) caused by Paecilomyces lilacinus - Xiao-liang Li; Chu-long Zhang; Wei-huan Fang; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2008)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Characteristics of Carbonaceous Aerosol at Taichung Harbor, Taiwan during Summer and Autumn Period of 2005 - Guor-Cheng Fang; S. C. Lee; Wen-Jhy Lee; Yan Cheng; I-Cherng Lin (Environmental Monitoring and Assessment, 2007)

Cloning and identification of partial DNA fragment for the B mating-type factor in Lentinula edodes using degenerate PCR - An-Zheng Li; Xue-Feng Xu; Fan-Xue Lin; Shui-Ming Cheng; Fang-Can Lin (World Journal of Microbiology and Biotechnology, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Atmosphic pollutants study of particles ionic species during high wind speed (>7 m s-1) near Taiwan strait in central Taiwan from 2004 to 2005 - Guor-Cheng Fang; Yuh-Shen Wu; Wen-Jhy Lee; Chi-Kwong Lin; Chung-Po Lin (Environmental Monitoring and Assessment, 2007)

A fine physical map of the rice chromosome 5 - Chia-Hsiung Cheng; Mei-Chu Chung; Shu-Mei Liu; Shi-Kuang Chen; Fang-Yi Kao; Shu-Jen Lin; Shin-Hsin Hsiao; I-Chieh Tseng; Yue-Ie C. Hsing; Hong-Pang Wu; Ching-San Chen; Jei-Fu Shaw; et al. (Molecular Genetics and Genomics, 2005)

Nucleotide Sequences and Functions of the Epstein-Barr Virus Latent Membrane Protein 1 Genes Isolated from Salivary Gland Lymphoepithelial Carcinomas - Kai Yu Jen; Masaya Higuchi; Jun Cheng; Jiang Li; Lan Yan Wu; Ying Fang Li; Han Liang Lin; Zhilong Chen; Vladimir Gurtsevitch; Masahiro Fujii; Takashi Saku (Virus Genes, 2005)

Transgenic tomato plants expressing the Arabidopsis NPR1 gene display enhanced resistance to a spectrum of fungal and bacterial diseases - Wan-Chi Lin; Ching-Fang Lu; Jia-Wei Wu; Ming-Lung Cheng; Yu-Mei Lin; Ning-Sun Yang; Lowell Black; Sylvia K. Green; Jaw-Fen Wang; Chiu-Ping Cheng (Transgenic Research, 2004)

Eudragit E Accelerated the Diketopiperazine Formation of Enalapril Maleate Determined by Thermal FTIR Microspectroscopic Technique - Shun-Li Wang; Shan-Yang Lin; Ting-Fang Chen; Wen-Ting Cheng (Pharmaceutical Research, 2004)

Cloning and Characterization of the First Cnidarian ADP-Ribosylation Factor, and Its Involvement in the Aiptasia-Symbiodinum Endosymbiosis - Ming-Chyuan Chen; Ying-Min Cheng; Li-Hsueh Wang; Chorng-Horng Lin; Xing-Yan Huang; Ming-Chin Liu; Ping-Jyun Sung; Lee-Shing Fang (Marine Biotechnology, 2004)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)